The employment relations challenges of an ageing workforce - Parry, Emma; Harris, Lynette (Birmingham, 2011)
"Demographic shifts create challenges for society and social policy. One of the most dynamic changes currently occurring in the workplace is the increasing number of older workers. Health, economic, social and legislative changes are contributing to this trend, which is set to present opportunities and challenges over the forthcoming decade."